Charge carrier loss mechanisms in CuInS2/ZnO nanocrystal solar cells. Issue 24 (2nd June 2016) - Scheunemann, Dorothea; Wilken, Sebastian; Parisi, Jürgen; Borchert, Holger
Abstract : The charge carrier loss mechanisms in solution-processed CuInS2 /ZnO nanocrystal solar cells are studied using steady-state and transient techniques. The results represent a step forward in understanding the device physics of copper-based nanocrystal photovoltaics. Abstract : Heterojunction solar cells based on colloidal nanocrystals (NCs) have shown remarkable improvements in performance in the last decade, but this progress is limited to merely two materials, PbS and PbSe. However, solar cells based on other material systems such as copper-based compounds show lower power conversion efficiencies and much less effort has been made to develop a better understanding of factors limiting their performance. Here, we study charge carrier loss mechanisms in solution-processed CuInS2 /ZnO NC solar cells by combining steady-state measurements with transient photocurrent and photovoltage measurements. We demonstrate the presence of an extraction barrier at the CuInS2 /ZnO interface, which can be reduced upon illumination with UV light. However, trap-assisted recombination in the CuInS2 layer is shown to be the dominant decay process in these devices.